Injustice in Family Relationships in The Novel “An American Marriage” (2018) by Tayari Jones - Ilyas, Febiana Sahroni; Rozani, An Fauzia (Universitas Negeri Padang, 2024)
This research explores injustice in family relationships through a psychoanalytic analysis of the novel An American Marriage (2018) by Tayari Jones. The research examines the impact of the injustice experienced by the character Roy and how it affects his family relationships. This research uses Freud's theory of psychoanalysis. This research is a content analysis research. The data used are quotations from the novel which are analyzed using elements such as character, and plot (conflict). This research aims to reveal the deeper meaning of injustice in family relationships and its impact on the dynamics of interpersonal life. By examining the novel's depiction of the long-term consequences of injustice, the research provides insights into such injustice. This analysis highlights the importance of addressing and mitigating injustice within a law to encourage a more just and supportive environment.